Accuracy and reproducibility of the O-RADS MRI risk stratification system based on enhanced non-DCE MRI in the assessment of adnexal masses. Issue 159 (February 2023) - Wu, Minrong; Tang, Qiying; Cai, Songqi; Zhu, Liuhong; Lin, Chong; Guan, Yingying; Rao, Shengxiang; Zhou, Jianjun
Highlights: O-RADS MRI risk stratification system could predict malignancy of adnexal masses. The scoring system based on enhanced non-DCE MRI has excellent reproducibility. Enhanced non-DCE MRI could perform well in evaluating adnexal malignancy. Abstract: Objective: Evaluation of the diagnostic performance and reproducibility of the Ovarian-Adnexal Reporting and Data System (O-RADS) Magnetic Resonance Imaging (MRI) risk stratification system based on enhanced non-dynamic contrast-enhanced (non-DCE) MRI in the diagnosis of adnexal masses. Methods: Patients who underwent conventional pelvic enhanced non-DCE MRI examination within one month prior to surgery formed the study population. Two experienced radiologists independently evaluated the images and assigned a score according to the O-RADS MRI risk stratification system. One of the radiologists reviewed the images and reassigned the scores after three months. Intra- and inter-observer agreement was evaluated with the k coefficient value. The adnexal masses that attained scores between 1 and 3 were considered benign, while those with scores of 4 or 5 were considered malignant. Analyses were conducted to determine the sensitivity, specificity, positive and negative predictive values, and receiver operating characteristic (ROC) curve, which were then used for evaluating the diagnostic efficacy of the developed system based on enhanced non-DCE MRI scan. The reference standard was histology. Results: A total of 308 patients (mean age: 42.09 ± 12.42 years, age range: 20–84 years) were enrolled in the study. Among the 362 adnexal masses from the included patients, there were 320 benign masses and 42 malignant masses. In the case of three readers, there were no malignant tumors scored 1–2. The O-RADS MRI score ≥ 4 was associated with malignancy resulted in a good diagnostic efficacy with the areas under the curve (AUC) values of 0.918 (95 % CI, 0.864–0.972), 0.905 (95 % CI, 0.842–0.968), and 0.882 (95 % CI, 0.815–0.950), the sensitivity values of 90.5 % (95 % CI, 87.5–93.5 %), 85.7 % (95 % CI, 82.1–89.3 %), and 83.3 % (95 % CI, 79.5–87.2 %), and the specificity values of 93.1 % (95 % CI, 90.5–95.7 %), 95.3 % (95 % CI, 93.1–97.5 %), and 93.1 % (95 % CI, 90.5–95.7 %) obtained for the three readers, respectively. Excellent intra-observer agreement and inter-observer agreement were observed with the k values of 0.883 (95 % CI, 0.814–0.952) and 0.848 (95 % CI, 0.770–0.926), respectively. Conclusions: The O-RADS MRI risk stratification system based on enhanced non-DCE MRI scans exhibited high accuracy and reproducibility in the prediction of adnexal masses malignancy. Enhanced non-DCE MRI scan may offer an alternative diagnostic tool when DCE is not possible.